If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -22 = 3 + 5u Solving -22 = 3 + 5u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-5u' to each side of the equation. -22 + -5u = 3 + 5u + -5u Combine like terms: 5u + -5u = 0 -22 + -5u = 3 + 0 -22 + -5u = 3 Add '22' to each side of the equation. -22 + 22 + -5u = 3 + 22 Combine like terms: -22 + 22 = 0 0 + -5u = 3 + 22 -5u = 3 + 22 Combine like terms: 3 + 22 = 25 -5u = 25 Divide each side by '-5'. u = -5 Simplifying u = -5
| 1/2+(2/3/3/4)-(4/5*5/6)= | | -4(4+6b)=80 | | 5z^3-15z^2-1520z=0 | | 2.9=6.9-0.8x | | 3m-3-5=-20 | | 35t=50t-37.5 | | (6xy^2-xy)(6xy^2+xy)= | | 4(y+1)=-6 | | x^2-2x+10=y | | 5x+2x-5=44 | | 7t^3-21t^2-2926t=0 | | 9+5x=4x+12 | | -4+5w=-14 | | 8x+9x-52=104-9x | | -(x-8)=3(-3x+4) | | 8=Xsquared-5x+8 | | 120+30m=80+50m | | 5-x=18+3x | | 4+2.5x=6.5x+2 | | -1+3-x=4+2x | | 28.75=6g+3.97 | | -6(2n-1)=-66 | | a+4+4a=14 | | 2g+16=2g+28 | | 8g=4+10g | | 1/2+(2/3+3/4)-4/5*5/6= | | 3(v+8)-5v=6 | | .25x+9.99=113.74 | | 5(y-1)=2(y-4)-6 | | 9y-6x=3+5x | | 7s-(3s+1)=4(s+s) | | -2(n-5)+4n=17 |